Deconvolution method to split up X-ray peaks emitted by 223Ra - Rafael Figueiredo Pohlmann Simões; Carlos José da Silva; Ronaldo Lins da Silva; Roberto Poledna; Paulo Alberto Lima da Cruz; Lídia Vasconcellos de Sá (Brazilian Journal of Radiation Sciences, 2018)
The Radium-223 (223Ra) has being used as a medicine for localized treatment of patients with osteoblastic metastasis originated by prostate cancer resistant of castration or hormone refractory. For a better treatment with this radionuclide, clinical images are one path to turn achievable organ's dosimetry for each patient. The X-rays emitted by 223Ra demonstrated as the main way to turn the image acquiring feasible. In order to study this X-ray area, deconvolution is necessary to split up the mains X-ray peaks that are measured by a high-purity germanium detector as doublet peaks in a complex region of the spectrum below 100 keV. For this, the Colegram® code was applied using the Low Energy X Voigt fitting curve on raw data source from Maestro® software. Results of activity using the deconvolution data from this work were in agreement with values obtained at absolute standardization live-time anticoincidence counting. The Colegram® code demonstrates a powerful tool to aid Maestro to split up the mains overlapped X-rays emitted by 223Ra.